Breaking Bad News: A Small-Group Learning Module and Simulated Patient Case for Preclerkship Students - Jamie A. Cvengros; Jay M. Behel; Ellenkate Finley; Rebecca Kravitz; Mark Grichanik; Rupel Dedhia (Association of American Medical Colleges, 2016)
Abstract Introduction Breaking bad news is a difficult skill that can elicit significant distress among learners. As such, it is important for learners to practice this skill in a controlled environment, which affords time to address any distress that arises and the opportunity to receive supportive feedback on performance. This breaking bad news module was designed for preclerkship students with previous training in basic communication skills and served as capstone to the preclerkship portion of the communication skills curriculum. Methods The small-group session was delivered to groups of 10-12 students and facilitated by a faculty member with expertise in communication skills. The small-group session included approximately 60 minutes of didactics and discussion, followed by a 30-minute faculty demonstration with simulated patients (SPs). Learners then had 30 minutes to practice with the SPs and received constructive feedback from the SPs and the faculty facilitator. Approximately 1 week following the small-group module, learners participated in an individual encounter with an SP and were assessed on physical examination skills and communication skills. Learners received detailed evaluations and feedback on breaking bad news skills from the SPs. Finally, learners had individual feedback meetings with their faculty facilitator, who reviewed the videotaped encounters, focusing on performance and experience of breaking bad news to the SP. Results In the 2015-2016 academic year, 217 medical students participated in this module. Learners demonstrated proficiency in the physical exam skills with 90% of learners asking about 5/8 components of the presenting complaint and 85% performing 5/8 physical exam maneuvers correctly. Similarly learners demonstrated expected levels of competence in interpersonal and communication skills. Discussion This learning exercise provided training in a critical communication skill but also supplied a framework for assessing and responding to personal and patient distress.